Solid Dispersions Incorporated into PVP Films for the Controlled Release of Trans-Resveratrol: Development, Physicochemical and In Vitro Characterizations and In Vivo Cutaneous Anti-Inflammatory Evaluation - Riccio, Bruno Vincenzo Fiod [UNESP]; Do Nascimento, André Luiz Carneiro Soares [UNESP]; Meneguin, Andréia Bagliotti [UNESP]; Rodero, Camila Fernanda [UNESP]; Santos, Kaio Pini [UNESP]; Sábio, Rafael Miguel [UNESP]; de Annunzio, Sarah Raquel [UNESP]; Fontana, Carla Raquel [UNESP]; Barud, Hernane da Silva; Ferrari, Priscileila Colerato; Chorilli, Marlus [UNESP] (MDPI, 2022)
Trans-resveratrol can promote various dermatological effects. However, its high crystallinity decreases its solubility and bioavailability. Therefore, solid dispersions have been developed to promote its amorphization; even so, they present as powders, making cutaneous controlled drug delivery unfeasible and an alternative necessary for their incorporation into other systems. Thus, polyvinylpyrrolidone (PVP) films were chosen with the aim of developing a controlled delivery system to treat inflammation and bacterial infections associated with atopic dermatitis. Four formulations were developed: two with solid dispersions (and trans-resveratrol) and two as controls. The films presented with uniformity, as well as bioadhesive and good barrier properties. X-ray diffraction showed that trans-resveratrol did not recrystallize. Fourier-transform infrared spectroscopy (FT-IR) and thermal analysis evidenced good chemical compatibilities. The in vitro release assay showed release values from 82.27 ± 2.60 to 92.81 ± 2.50% (being a prolonged release). In the in vitro retention assay, trans-resveratrol was retained in the skin, over 24 h, from 42.88 to 53.28%. They also had low cytotoxicity over fibroblasts. The in vivo assay showed a reduction in inflammation up to 66%. The films also avoided Staphylococcus aureus’s growth, which worsens atopic dermatitis. According to the results, the developed system is suitable for drug delivery and capable of simultaneously treating inflammation and infections related to atopic dermatitis.
Keywords: amorphization; anti-inflammatory activity; antimicrobial effect; crystallinity; skin permeation; solubility; technological innovation